Pengaruh Perbedaan Jenis Pelarut terhadap Kandungan Senyawa Kimia, Aktivitas Antioksidan, dan Kadar Sitotoksisitas dari Ekstrak Gum Acacia Decurrens Willd. - Ramadhany Ayu Purnama; Sigit Sunarta; Hilda Ismail (Jurnal Ilmu Kehutanan, 2022)
This study aimed to determine the chemical compounds in A. decurrens gum and its bioactivity potential. Extraction was carried out in multilevel with the reflux technique using n-hexane, ethanol, and water as solvents. The chemical compounds were identified using Gas Chromatography-Mass Spectrometry (GC-MS). The amount of A. decurrens gum extract yield, total phenolic content (TPC), total flavonoid content (TFC), and total flavonols content (TVC) were then analyzed quantitatively. Furthermore, bioactivity in the form of antioxidant activity was analyzed with the 2,2-diphenyl-1-picrylhydrazil (DPPH) method, while the cytotoxicity level was assessed using the brine shrimp lethality assay (BSLT). The GC-MS analysis showed that the n-hexane-soluble fraction contained alkane, alkene, aldehyde, ester, and aromatics, while the ethanol-soluble fraction contained monosaccharide and fat group compounds. The water-soluble fraction contained only the monosaccharide group. The highest content value was obtained from the ethanol-soluble fraction, namely TPC, TFC, TVC, and antioxidant activity of 19.61±0.47 mgGA/g, 23.89±1.32 mgQE/g, 13.41±0.81 mgCE/g, and IC50: 3.842 g/mL, respectively. The cytotoxicity content obtained from each fraction sequentially was 0.47 ppm, 5.91 ppm, and 6.56 ppm for n-hexane, ethanol, and water, respectively.